HUBUNGAN SOSIAL BUDAYA DENGAN PEMBERIAN ASI EKSKLUSIF DIWILAYAH KERJA PUSKESMAS PABATU KOTA TEBING TINGGI TAHUN 2019 - TRIE ULFA NUANSA SINAGA; SAMSIDAR SITORUS; JITASARI TARINGAN SIBERO (JURNAL ILMIAH SIMANTEK, 2020)
World Health Organizations recommends exclusive breastfeeding for 6 months. Experts state that the benefits of breast milk will increase if the baby is only given it for the first 6 months of life. The low coverage of exclusive breastfeeding has a relationship with social culture. The purpose of this study was to determine the socio-cultural relationship with exclusive breastfeeding.This research uses quantitative research with cross sectional approach. The populations were all mothers who have babies aged 7-12 months at Working Area of Pabatu Health Center Tebing Tinggi amount 324 people. The numbers of sample were 76 respondents with random sampling techniques. Data analysis used univariate, bivariate and multivariate analyzes.The results of the social cultural Chi Square test include education with p-value .026, work with p-value .082, income with p-value .031, knowledge with p-value .005, confidence with p-value .054, customary with p-value .003 and family support with p-value .028. This showed the variables that have a relationship with exclusive breastfeeding seen from p-value <.05, namely education, income, knowledge, habits, family support and that were not related to exclusive breastfeeding p-value > .05, namely work and trust.Final logistic regression test found education, knowledge, habits, and family support with p-value <.05, and the most dominant is the habit variable. It is expected that the government of Tebing Tinggi City will have a more vigorous campaign in conducting the importance of exclusive breastfeeding.